2014
DOI: 10.1093/ageing/afu021
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the 4AT, a new instrument for rapid delirium screening: a study in 234 hospitalised older people

Abstract: Objective: to evaluate the performance of the 4 ‘A’s Test (4AT) in screening for delirium in older patients. The 4AT is a new test for rapid screening of delirium in routine clinical practice.Design: prospective study of consecutively admitted elderly patients with independent 4AT and reference standard assessments.Setting: an acute geriatrics ward and a department of rehabilitation.Participants: two hundred and thirty-six patients (aged ≥70 years) consecutively admitted over a period of 4 months.Measurements:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
467
2
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(519 citation statements)
references
References 24 publications
9
467
2
23
Order By: Relevance
“…9 The detection of cognitive impairment should always be accompanied by an assessment for delirium, for example using the 4-AT. 10 Delirium has acute onset, typically over days and weeks. Failed detection is associated with a sevenfold hazard for increased mortality, 11,12 and is an independent predictor of hospital length of stay.…”
Section: Delirium and Dementiamentioning
confidence: 99%
“…9 The detection of cognitive impairment should always be accompanied by an assessment for delirium, for example using the 4-AT. 10 Delirium has acute onset, typically over days and weeks. Failed detection is associated with a sevenfold hazard for increased mortality, 11,12 and is an independent predictor of hospital length of stay.…”
Section: Delirium and Dementiamentioning
confidence: 99%
“…1 However, their recommendation of these assessments are not specific to HF and a recent systematic review concluded that the accuracy of normative values for these tests in HF need to be established, 24 work that is currently underway by the4AT.com) as a quick screening tool for cognitive impairment and delirium. 25 This is a validated tool routinely used in clinical practice internationally to detect delirium with good sensitivity and specificity.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…[33] Common examples include the CAM, 4AT, Nursing Delirium Screening Scale (Nu-DESC), and NEECHAM Confusion Scale. [4,[36][37][38] These instruments are mostly designed to be completed by nurses and incorporate information obtained from patient observation, caregivers, or the medical record. The CAM tool is standardized and widely accepted owing to its brevity and reliability (see Figure 1).…”
Section: Recognition Toolsmentioning
confidence: 99%